Comparison of the prevalence of antimicrobial-resistant Escherichia coli, verotoxin-producing E. coli and enteropathogenic E. coli in griffon vultures (Gyps fulvus), cinereous vultures (Aegypius monachus) and red kites (Milvus milvus) fed in the wild and in a rescue centre - Cerezo-Caro, Alejandra; Mas, Alicia; González-González, Fernando; Rodríguez-Carrión, Andrea; Flament-Simon, Saskia C.; Blanco, Jesús E.; Martínez-Rodrigo, Abel; Hurtado-Morillas, Clara; Domínguez-Bernal, Gustavo; Orden, José A. (Frontiers in Veterinary Science, 2025)
IntroductionAntimicrobial resistance in Escherichia coli from avian scavengers remains poorly characterized, with limited data available for griffon vultures (Gyps fulvus) and no studies on cinereous vultures (Aegypius monachus) or red kites (Milvus milvus). In addition, the presence of verotoxin-producing E. coli (VTEC) and enteropathogenic E. coli (EPEC), both zoonotic pathogens, in these animal species has not been studied before.MethodsA total of 282 E. coli isolates were recovered from faecal samples of 28 griffon vultures, 22 cinereous vultures and 13 red kites. Isolates were tested for resistance to 14 antimicrobial agents and screened for vt1, vt2, and eae genes. Sampling was performed upon arrival at a wildlife rescue centre and after several weeks of housing that centre.ResultsHigh levels of antimicrobial resistance (25–50%) were detected for amoxicillin-clavulanic acid, ceftriaxone, tetracycline, trimethoprim-sulphamethoxazole and nalidixic acid, and very high (>50%) for ampicillin, streptomycin, kanamycin, amikacin, gentamicin, sulphafurazole and ciprofloxacin. No significant differences in antimicrobial resistance prevalence were observed between initial and follow-up samplings. In addition, two VTEC isolates were detected in a cinereous vulture, and five EPEC isolates were identified in a griffon vulture and four cinereous vultures. All VTEC and EPEC isolates were detected in a single sampling event.ConclusionThese findings indicate that vultures and red kites are an important reservoir of antimicrobial-resistant E. coli. Measures should be implemented to minimize their exposure to antimicrobials or antimicrobial-resistant bacteria in both natural environments and rescue centres. Furthermore, the detection of VTEC and EPEC suggests that vultures may act as occasional carriers of zoonotic E. coli, highlighting potential public health concerns.